A comprehensive investigation on micro-structured surfaces for underwater drag reduction. (15th December 2020) - Wu, Tao; Chen, Wei; Zhao, Aiguo; He, Peng; Chen, Hong
Abstract: Micro-structured surfaces are desirable in achieving good drag reduction performance for underwater applications. In the study, comprehensive investigation including numerical study, application analysis, precision manufacturing and accurate drag measurement of micro-structured surfaces have been taken for better understanding of drag reduction mechanisms. Five types of micro grooves are firstly proposed and comparisons of respective hydrodynamic performance reveal that the rectangle grooves perform the best, followed by the semicircular ones, the triangle ones, shark skin, and the U-shaped grooves with 5° attack angle has the least effect. Theoretical calculation of optimal groove width has been conducted for application analysis and the optimal groove width decreases dramatically with travel speed, while as increases slightly along with the increasing vehicle length. Considering both drag reduction ability and manufacturing feasibility, the semicircular grooves are emphasized and micro fly milling is adopted for high-precision machining four groups of grooves. Drag reduction tests of these grooves are conducted by a specially designed measuring system. Experimental results show that the smaller lateral spacing of grooves, the better hydrodynamic performance and S4 surfaces exhibits the maximum drag reduction rate with 27.7%. In case fluid velocities in the range of 0.5 m/s and 4.5 m/s, the averaged drag reduction rate is 13.05%. Highlights: The rectangle grooves give the best hydrodynamic performance, followed by the semicircular ones, the triangle ones, shark skin, and the U-shaped grooves with 5〫attack angle. The optimal groove width decreases dramatically with travel speed, while as increases slightly along with the increasing vehicle length. Micro fly milling is suitable for high-precision machining the proposed semicircular grooves. The smaller lateral spacing of grooves, the better hydrodynamic performance.